2011
DOI: 10.18553/jmcp.2011.17.8.596
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Comparative Effectiveness of 3 Oral Bisphosphonates in a Large Managed Care Organization: Adherence, Fracture Rates, and All-Cause Cost

Abstract: • Randomized, controlled trials (RCTs) of oral bisphosphonates have shown statistically significant reductions in fracture rates versus placebo, but whereas alendronate and risedronate have shown reductions in vertebral and nonvertebral fractures, ibandronate has been shown to reduce vertebral fractures only. Comparison of fracture rates among the bisphosphonates is difficult due to the lack of head-to-head RCTs designed to compare this outcome.• Several observational studies regarding osteoporosis therapy hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
14
1
1
Order By: Relevance
“…Briesacher and colleagues similarly did not find a significant effect on fracture risk in patients who switched from once weekly to once monthly bisphosphonates [21], and others found that switching bisphosphonates improved persistence overall, which would be expected to reduce fracture risk [7,19,20]. Our data also suggest that medication-taking patterns, even discontinuation, do not significantly impact fracture risk, which does not correspond to what others have found [8,[12][13][14][15][16][17][18]58]. We can propose reasons for our inability to detect a relationship between bisphosphonate discontinuations and fracture risk.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Briesacher and colleagues similarly did not find a significant effect on fracture risk in patients who switched from once weekly to once monthly bisphosphonates [21], and others found that switching bisphosphonates improved persistence overall, which would be expected to reduce fracture risk [7,19,20]. Our data also suggest that medication-taking patterns, even discontinuation, do not significantly impact fracture risk, which does not correspond to what others have found [8,[12][13][14][15][16][17][18]58]. We can propose reasons for our inability to detect a relationship between bisphosphonate discontinuations and fracture risk.…”
Section: Discussioncontrasting
confidence: 83%
“…In observational studies, the proportions of patients that persisted with therapy for 1 year are low for United States (US) cohorts (21.0-56.7%) and non-US cohorts (21.9-74.8%) [2][3][4][5][6][7][8][9][10][11]. Some studies have reported an association between low adherence or persistence and fracture outcomes or healthcare costs (i.e., higher fracture rates or higher costs in patients with lower adherence) [8,[12][13][14][15][16][17][18]. However, the effect of changing medications on osteoporosis health outcomes has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects were required to either have a medical claim with an OP diagnosis (ICD-9-CM 733.0x) or an OP-related fracture as evidenced by both an ICD-9-CM diagnosis code and CPT code [29][30][31] (see the supplementary Appendix for codes) between 1 January 2007 and 31 December 2011. Additionally, subjects were required to be continuously enrolled in any tracked health plan for all of 2011 and 2012.…”
Section: Study Samplementioning
confidence: 99%